Factors influencing employee turnover intention / Mohd Rusydi Abdul Rahim - Abdul Rahim, Mohd Rusydi (Faculty of Business and Management, 2018)
The title of this research is “Factors Influencing Employee Turnover Intention”. This study consists of one dependent variable which is Turnover Intention and four independent variables which are Job Satisfaction, Affective Commitment, Trust and Perceived Organizational Institution Support. The current economic condition has causes the employee turnover rate higher. Hence, the four internal factor were being tested whether it have significant affect turnover intention or not. The results were collected from 76 respondents through a questionnaire. A survey consisted of 25 questions that used Likert Scale questions to establishing measureable values from the respondent. The data analysis intends to determine whether there are significant effect between independent variables (Job Satisfaction, Affective Commitment, Trust and Perceived Organizational Institution Support) with dependent variable (Turnover Intention). The data was being analyzed using SPSS. Thus, this study has found that two independent variables which is Job Satisfaction and Trust has significant effect while two independent variable which is Affective Commitment and Perceived Organizational Support has no significant effect with dependent variable which is Turnover Intention.